2006
DOI: 10.1176/appi.ajp.163.12.2164
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cortisol and Progression of Dementia in Subjects With Alzheimer-Type Dementia

Abstract: Objective-Previous studies of subjects with dementia of the Alzheimer type (DAT) have reported correlations between increases in activity of the hypothalamic-pituitary-adrenal (HPA) axis and hippocampal degeneration. In this study, we sought to determine whether increases in plasma cortisol, a marker of HPA activity, were associated with clinical and cognitive measures of the rate of disease progression in DAT subjects.Method-Thirty-three subjects with very mild and mild DAT and 21 nondemented comparison subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
125
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(135 citation statements)
references
References 48 publications
5
125
0
5
Order By: Relevance
“…As described in other preclinical and clinical studies (Csernansky et al, 2006;Hebda-Bauer et al, 2013;Nasman et al, 1995;Rasmuson et al, 2001), we report an altered circadian rhythm of the HPA axis early in our mouse model. Whether this results from a dysregulation of the pulsatile ultradian pattern of CORT secretion is however yet to be demonstrated.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As described in other preclinical and clinical studies (Csernansky et al, 2006;Hebda-Bauer et al, 2013;Nasman et al, 1995;Rasmuson et al, 2001), we report an altered circadian rhythm of the HPA axis early in our mouse model. Whether this results from a dysregulation of the pulsatile ultradian pattern of CORT secretion is however yet to be demonstrated.…”
Section: Discussionsupporting
confidence: 79%
“…GR has a low affinity for CORT and is thus believed to be a key player under elevated CORT levels, although a role of MR cannot be excluded. Both AD patients and AD mouse models display a dysregulated HPA axis, marked by a mild hypercortisolemia that is apparent early during the pathology (Csernansky et al, 2006;Elgh et al, 2006;Hebda-Bauer et al, 2013;Nasman et al, 1995;Rasmuson et al, 2001;Weiner et al, 1997). Increased CORT levels are sufficient to exacerbate Ab deposits, and a recent study suggested that antagonism of GR could prevent this effect (Baglietto-Vargas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As stress and/or excessive glucocorticoid activity are linked with the exacerbation of AD symptoms (Wilson et al, 2005;Csernansky et al, 2006), loss of hippocampal mass (Lupien et al, 1998), and reduced neurogenesis in rodents (Tanapat et al, 2001;Ambrogini et al, 2002), inhibition of HSD1 may also slow disease progress. Additional studies in models of AD, such as APP-overexpressing mice, may offer further evidence of the potential for HSD1 inhibitors to act as both symptomatic and disease-modifying agents.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormally high levels of glucocorticoids are correlated with memory impairment in some patients with AD (Pomara et al, 2003) and depression (Bremmer et al, 2007). Increased glucocorticoid activity is also associated with greater hippocampal atrophy and memory impairment in the elderly (Lupien et al, 1998) and more rapid AD disease progression (Csernansky et al, 2006). Systemic administration of glucocorticoids increases ␤-amyloid formation and tau accumulation in transgenic AD mice (Green et al, 2006) and reduces neurogenesis in rats (Ambrogini et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Similar discrepancies have been observed in a number of other conditions, like multiple sclerosis and neurodegenerative disorders. For example, increased plasma cortisol levels have been associated with more rapid disease progression in subjects with Alzheimer-type dementia (AD) (Csernansky et al, 2006). In contrast, a large post-mortem neuropathological examination of individuals receiving systemic GCs for various medical reasons revealed at least 50% less histological markers of AD pathology compared to non-treated subjects (Beeri et al, 2012).…”
Section: Inconsistencies In Our Understanding Of Gc Therapeutics In Nmentioning
confidence: 99%